Análise físico-química, microbiológica e sensorial de cultivares de feijão - Oliveira, Viviani Ruffo de (2009)
The objectives of this work were: (1) to evaluate the nutritional and microbiological quality of common beans (Phaseolus vulgaris L.) processed with or without soaking water; (2) to analyze the sensorial traits of common bean cultivars and to compare the efficiency of quantitative descriptive analysis with not-trained and trained people; (3) to investigate the sensorial traits of common bean cultivars and to compare the efficiency of quantitative descriptive analysis with not-trained and trained people;(4) to evaluate the effect of storage under refrigeration during six months on the cooking quality, the content of minerals and the darkness of common bean cultivars with black and color tegument. Grains of Iraí and BRS Expedito beans cultivars were submitted to soaking in distilled water for eight hours, at environmental temperature. The cooking was made with the use or discard of soaking water. The minerals were determined in the grains and in the broth separately, and the microorganisms, in the mixture of grains and broth. The sensorial analysis was carried with grains of four common bean cultivars: BRS Expedito, BRS Campeiro, Iraí and Carioca. Each common bean sample was macerated for eight hours and the water was separated of the grains and placed under firing in pressure pan. The not-trained and trained people received 25 g of the four cooked cultivars and the analysis was taken using an evaluation file following the technique of Quantitative Descriptive Analysis. To evaluate the cooking time, it was used four cultivars of beans: BRS Expedito, BRS Campeiro, Pérola and Carioca and the cooking was carried through in a domestic pressure pan during 15, 20, 25 or 30 minutes. The sensorial analysis was effected in two stages: training for Qualitative Descriptive Analysis and the sensorial analysis properly, with seven trained panel. It was used six cultivars (Macanudo, Guapo Brilhante, BRS Campeiro, Pérola, Carioca and LH 5) and three times of storage (0, 3 and 6 months). It was evaluated the cooking quality (water absorption, normal and hard grains and cooking time), the mineral content and the grain clarity ( L value). According to the results, minerals composition in the grains and in the bean broth were not modified by the discarding maceration water. The bean broth presented high amount of potassium, magnesium and sulphur content. The discard of the soaking water did not improve microbiological quality of the processed common bean. Iraí and BRS Expedito cultivars may be cooked with the use or discard of soaking water because minerals content and microbiological quality of the processed common bean are maintained. The sensorial attributes texture and bean broth were evaluated with the highest experimental precision to the trained people, because lesser coefficient of variation and error mean squares were observed. The not-trained people discriminate greater number of sensorial attributes in common bean cultivars, but with a reduced amount of experimental precision. The trained group recognizes differences in the texture and broth the beans, with highest experimental precision. The panel recognized differences among the cultivars such as: uniformity tegument color, hardness, graininess, broth color and viscosity. The rupture of the tegument of the grains was bigger as it was increased the cooking time. The hardness and the graininess received best notes as longer as the cooking time of the common bean. The use of 20 the 25 minutes to cook in domestic pressure pan seems to identify black and carioca cultivars of common bean with the best evaluation profile, besides keeping the integrity of the cooked grains. Beans storage for six months reduces the grains capacity of water absorption and influences negatively in the darkness of Carioca group. However, it does not increase the amount of hardshell grains and the cooking time, as well as the minerals content of the grains.